2012
DOI: 10.1523/jneurosci.1040-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-Like Behavior of Prenatally Stressed Rats Is Associated with a Selective Reduction of Glutamate Release in the Ventral Hippocampus

Abstract: Abnormalities of synaptic transmission and plasticity in the hippocampus represent an integral part of the altered programming triggered by early life stress. Prenatally restraint stressed (PRS) rats develop long-lasting biochemical and behavioral changes, which are the expression of an anxious/depressive-like phenotype. We report here that PRS rats showed a selective impairment of depolarization-or kainate-stimulated glutamate and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 89 publications
8
74
0
3
Order By: Relevance
“…Prenatal stress has been reported to decrease the expression of synaptophysin and other synaptic proteins in the hippocampus of adult male (Marrocco et al 2012) and female rat offspring (Biala et al 2011), but these same effects have not been found in male and female marmosets (Law et al 2008). Differences between our findings and that of previous work in rats may be that we analyzed specific regions for overall density levels of synaptophysin within the dorsal hippocampus, whereas previous work investigated synaptophysin levels in the entire hippocampus by western blotting (Biala et al 2011) or only in the ventral hippocampus (Marrocco et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal stress has been reported to decrease the expression of synaptophysin and other synaptic proteins in the hippocampus of adult male (Marrocco et al 2012) and female rat offspring (Biala et al 2011), but these same effects have not been found in male and female marmosets (Law et al 2008). Differences between our findings and that of previous work in rats may be that we analyzed specific regions for overall density levels of synaptophysin within the dorsal hippocampus, whereas previous work investigated synaptophysin levels in the entire hippocampus by western blotting (Biala et al 2011) or only in the ventral hippocampus (Marrocco et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in hippocampal synaptic transmission and plasticity lie at the core of the pathological phenotype induced by prenatal stress (Yaka et al, 2007;Mairesse et al, 2012;Marrocco et al, 2012Marrocco et al, , 2014. Prenatally restraint stressed (PRS) rats, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…PRS in rodents causes a series of neuroplastic changes, which might be considered as "maladaptive," and recapitulate some of the features of anxious/depressive disorders and schizophrenia (Maccari et al, 1995;Morley-Fletcher et al, 2003;Marrocco et al, 2012;Matrisciano et al, 2012a,b). Here, we have shown that adult PRS rats are highly resistant to catalepsy induced by haloperidol, one of the most widely used drugs in the treatment of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The model of prenatal restraint stress (PRS) in rodents recapitulates features of major psychiatric disorders, such as depression, anxiety, and schizophrenia (Maccari et al, 1995;Morley-Fletcher et al, 2003, 2011Marrocco et al, 2012;Matrisciano et al, 2012a,b). Adult "PRS rats," i.e., the offspring of mothers exposed to repeated episodes of restraint stress during pregnancy, show a deregulation of the hypothalamicpituitary-adrenal axis, which leads to an increased glucocorticoid secretion in response to stress (Darnaudery and Maccari, 2008).…”
Section: Introductionmentioning
confidence: 99%